Antibiotic stories: a mixed-methods, multi-country analysis of household antibiotic use in Malawi, Uganda and Zimbabwe - Justin Dixon; Shunmay Yeung; John Bradley; Laurie Denyer Willis; Susan Nayiga; Clare I R Chandler; Rashida Abbas Ferrand; Sham Lal; Miriam Kayendeke; Christine Nabirye; Sarah G Staedke; Eleanor Elizabeth MacPherson; et al. (BMJ Global Health)
Background As concerns about the prevalence of infections that are resistant to available antibiotics increase, attention has turned toward the use of these medicines both within and outside of formal healthcare settings. Much of what is known about use beyond formal settings is informed by survey-based research. Few studies to date have used comparative, mixed-methods approaches to render visible patterns of use within and between settings as well as wider points of context shaping these patterns.Design This article analyses findings from mixed-methods anthropological studies of antibiotic use in a range of rural and urban settings in Zimbabwe, Malawi and Uganda between 2018 and 2020. All used a ‘drug bag’ survey tool to capture the frequency and types of antibiotics used among 1811 households. We then undertook observations and interviews in residential settings, with health providers and key stakeholders to better understand the stories behind the most-used antibiotics.Results The most self-reported ‘frequently used’ antibiotics across settings were amoxicillin, cotrimoxazole and metronidazole. The stories behind their use varied between settings, reflecting differences in the configuration of health systems and antibiotic supplies. At the same time, these stories reveal cross-cutting features and omissions of contemporary global health programming that shape the contours of antibiotic (over)use at national and local levels.Conclusions Our findings challenge the predominant focus of stewardship frameworks on the practices of antibiotic end users. We suggest future interventions could consider systems—rather than individuals—as stewards of antibiotics, reducing the need to rely on these medicines to fix other issues of inequity, productivity and security.